2020
DOI: 10.1097/iae.0000000000002338
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Acute Nontraumatic Vitreous Hemorrhage in Healthy Patients

Abstract: Purpose: To compare outcomes in dense vitreous hemorrhage versus mild vitreous hemorrhage due to nontraumatic posterior vitreous detachment. Methods: We compared 315 eyes, divided into 2 patient groups, one with dense and the other with mild vitreous hemorrhage. The main outcome measures were final mean best-corrected visual acuity, number of retinal tears, number of retinal detachments, and the number of pars plana vitrectomy and/or scleral buckle surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…21 Our series did not highlight significant differences in final BCVAs between the early PPV group and the conservative/late PPV groups and in any of the diagnostic subgroups, in agreement with previous literature. 22 Nevertheless, our results suggest that significant improvements in final BCVA may be expected in the group treated with early PPV (p = 0.00001).…”
Section: Discussionmentioning
confidence: 60%
“…21 Our series did not highlight significant differences in final BCVAs between the early PPV group and the conservative/late PPV groups and in any of the diagnostic subgroups, in agreement with previous literature. 22 Nevertheless, our results suggest that significant improvements in final BCVA may be expected in the group treated with early PPV (p = 0.00001).…”
Section: Discussionmentioning
confidence: 60%
“…A previous prospective study has reported that vitreous detachment and traction to a retinal vessel were the most common causes of vitreous hemorrhage [ 10 ]. Pighin et al [ 11 ] reported that retinal tears were found in 65.8% of healthy patients with dense vitreous hemorrhage. Although these findings differ from our result, the proportion of patients with well-controlled hypertension in these studies was 16% [ 10 ] and 21.7% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pighin et al [ 11 ] reported that retinal tears were found in 65.8% of healthy patients with dense vitreous hemorrhage. Although these findings differ from our result, the proportion of patients with well-controlled hypertension in these studies was 16% [ 10 ] and 21.7% [ 11 ]. In the present report, 44% of patients had systemic hypertension, a well-known, classic risk factor of BRVO [ 12 ].…”
Section: Discussionmentioning
confidence: 99%